EDUCATIONAL DATA MINING (KONSEP DAN PENERAPAN) - Marisa, Fitri (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2013)
Electronic Learning (E-Elarning), especially Web-based learning or intelligent tutorial system has yielded information about the interaction between students and the system. This information is stored in a database in the form of a web log. Within a certain period it will be a large amount of information. From the collection of large amounts of data that can be explored using data mining methods to generate new patterns that can be useful for improving the effectiveness of computer-based learning process. This paper will discuss how data mining can be utilized to improve the effectiveness of computer-based learning process. In its application the data will be processed in three stages: the collection, transformation, and analysis. Then the techniques used in the analysis algorithm is Association rules, classification, and clustering. Keywords: data mining, Educational data mining, E-Learning